Ensino de física potencializado pela aprendizagem da linguagem de programação python: uma sequência didática baseada nos três momentos pedagógicos - Yamaguti, Mateus Xavier (2024)
Understanding the need to renew current physics teaching, with the use of innovative strategies such as the use of digital resources, this qualitative and exploratory research seeks to discuss the potential that the Python programming language has in teaching Physics combined with methodology of teaching the Three Pedagogical Moments (3PM). For this, the Case Study research methodology was used, applied to a group of high school students from a public school in the interior of the state of São Paulo during the after-school shift remotely. To make this research possible, the research professor developed digital teaching materials and resources with the aim of enhancing teaching, and also achieving the development of Scientific Literacy and Technology (SLT) in students, relating the concepts of Physics and programming language Python, supported by 3PM. From the content analysis of the data constituted in the research, it was possible to establish three categories, signs of learning in Physics and/or programming, problematization and/or application of the subjects covered in class and indications of potential or limitations of teaching Physics with programming. Finally, these categories revealed that there are potentialities such as promoting the understanding of physical concepts and visualization of their phenomena. However, there is still a need to create resources and strategies that minimize the initial impact of the programming language and promote greater affinity with the student audience.